Manajemen Penilaian Kinerja Guru - Aswaruddin Aswaruddin (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study is to discuss the assessment of teacher performance. This research method is the literature review. The results showed that the Teacher Competency Standards were developed as a whole from 4 main competencies, namely pedagogic, personality, social, and professional competencies. The fourth competency is integrated into teacher performance. There are indicators of teaching skills by the teacher, namely, a) questioning skills; b) skills to provide reinforcement (reinforcement skills); c) the skill of making variations; d) explaining skills (explaining skills); e) skills to open and close lessons (set induction and closure skills); f) skills to guide small group discussions; g) classroom management skills; h) individual learning skills. In conclusion, teacher performance has certain specifications or criteria. Teacher performance can be seen and measured based on specifications or competency criteria that must be possessed by every teacher. Keywords: Management, Performance Appraisal